A Fully Implicit Finite Volume Lattice Boltzmann Method for Turbulent Flows (Communications in Computational Physics, 2018)
Almost all schemes existed in the literature to solve the Lattice BoltzmannEquation like stream & collide, finite difference, finite element, finite volume schemes areexplicit. However, it is known fact that implicit methods utilizes better stability andfaster convergence compared to the explicit methods. In this paper, a method namedherein as Implicit Finite Volume Lattice Boltzmann Method (IFVLBM) for incompressiblelaminar and turbulent flows is proposed and it is applied to some 2D benchmarktest cases given in the literature. Alternating Direction Implicit, an approximate factorizationmethod is used to solve the obtained algebraic system. The proposed methodpresents a very good agreement for all the validation cases with the literature data.The proposed method shows good stability characteristics, the CFL number is eased.IFVLBM has about 2 times faster convergence rate compared with Implicit-ExplicitRunge Kutta method even though it possesses a computational burden from the solutionof algebraic systems of equations.